Comportamento sexual de cabras Toggenburg durante a estação reprodutiva após luteólise natural ou induzida - Rute Maria de Paula Oliveira (2010)
Proestrus (days -2 and -1), estrus (days 1, 2 and 3) and metaestrus (days +1 and +2) sexual behavior was monitored in Toggenburg females goats, during natural breeding season after induced and natural luteolysis. The females received two doses of PGF2 10-day interval, for estrus synchronization. After the first injection the estrus was monitored three times a day with bucks. The females were classified into groups such as natural or synchronized estrus plus nulliparous, dry, and lactating does. Interest in male and tail wagging were observed as the apex during estrus. Interest in male and tail wagging were observed as the apex during estrus. The standing heat was the determinant behavior during estrus. Escape, tail low, and passivity (indifference to the male) were observed in high frequency in proestrus and metaestrus. Homosexuality, bleating, and raised tail showed the lowest frequencies and were not directly associated to any phase of the estrus cycle. The frequency of the behaviors was influenced only for the phase of the estrous cycle. The reproductive parameters of the estrus had been evaluated in accordance with the reproductive category of the female and the type of estrus (induced and inseminated, induced but not inseminated, and natural). The percentage of animals that showed estrus after the first and second injections of PGF2 was 85.48% and 88.71%, respectively. The duration of estrus was reduced in females inseminated. Approximately 50% of the estrus initiated in the morning. The reproductive parameters were not influenced by the reproductive category of the females. Progesterone concentrations were evaluated during the protocol of synchronization and for the pregnancy detection. The mean values of plasmatic progesterone of pregnant and non-pregnant females were 9.36±0.50 and 6.72±1.18ng/mL, respectively (P<0.05), from days 19th to 21st after the artificial insemination. The results presented sensitivity, specificity, and accuracy of 100%, 34.62%, and 67.92%, respectively, for the diagnosis of pregnancy confirmed for the transrectal ultrasound at same periods. The transrectal ultrasound at day 21 of gestation provided sensitivity, specificity, and accuracy of 80.95%, 72.73%, and 78.13%, respectively. The transrectal ultrasound provided more accurate pregnancy diagnosis than progesterone dosage at the same time. The weight, the corporal score, and the age of the females did not influence the conception rate